New species of Pseudosperma (Agaricales, Inocybaceae) from Pakistan revealed by morphology and multi-locus phylogenetic reconstruction - Saba, Malka; Haelewaters, Danny; Pfister, Donald H; Khalid, Abdul Nasir (MycoKeys, 2020)
During fungal surveys between 2012 and 2014 in pine-dominated forests of the western Himalayas in Pakistan, several collections of Pseudosperma (Agaricales, Inocybaceae) were made. These were documented, based on morphological and molecular data. During this work, three new species came to light, which are here formally described as Pseudosperma brunneoumbonatum, P. pinophilum and P. triacicularis. These species belong in the genus Pseudosperma fideMatheny et al. (2019) = Pseudosperma clade fideMatheny (2005) = Inocybe sect. Rimosae s.s. fideLarsson et al. (2009). Macro- and micro-morphological descriptions, illustrations and molecular phylogenetic reconstructions of the studied taxa are provided. The new species are differentiated from their close relatives by basidiospore size and colouration of basidiomata. Molecular phylogenetic relationships are inferred using ITS (ITS1-5.8S-ITS2), nrLSU and mtSSU sequence data. All three newly-described taxa likely share an ectomycorrhizal association with trees in the genus Pinus. In addition, five names are recombined in Inosperma, Mallocybe and Pseudosperma. These are Inosperma vinaceobrunneum, Mallocybe erratum, Pseudosperma alboflavellum, Pseudosperma friabile and Pseudosperma neglectum.
Keywords: taxonomy; southern Asia; Pinus roxburghii; Ectomycorrhizal fungi; phylogeny; molecular systematics